FINANCIAL ADMINISTRATION GOVERNANCE ANALYSIS AT THE SILAEN DISTRICT OFFICE TOBA REGENCY - Juriana Megawati Hutabarat; Aswin Akbar (SEAN Institute, 2023)
The purpose of this research is to ascertain the financial management structure of the Silaen District Office in the Toba Regency in the year 2022. Case study research employing a descriptive qualitative methodology was used for this study. The information used is a synopsis of the Silaen District Office, Toba Regency, 2020 budget as found in the office's annual report. Descriptive analysis was used in this investigation to help paint a clear picture by gathering and sorting data in great detail, then describing what was found. After compiling data, we can say that the Silaen District Office, Toba Regency's Financial Administration Governance follows Domestic Regulation No. 13 of 2006, Minister of Home Affairs Regulation No. 77 of 2020, Article 56 of Law No. 1 of 2004 of the Republic of Indonesia Relating to the State Treasury; Chapter IX of PP No. 58 of 2005 Relating to Regional Financial Management; Article 99 of the Regulation of the Minister of Home Affairs No. 13 of 2006 Relating to Guidelines for Regional Financial Management, Dated May 15, 2006; Part III of Chapter XII of the Regulation of the Minister of Home Affairs No. 64 of 2006 Relating to Regional Financial Management; and the Regulation of the Minister of Home Affairs.